2007
DOI: 10.1161/01.str.0000260090.90508.3e
|View full text |Cite
|
Sign up to set email alerts
|

High-Sensitivity C-Reactive Protein and Soluble CD40 Ligand as Indices of Inflammation and Platelet Activation in 880 Patients With Nonvalvular Atrial Fibrillation

Abstract: Background and Purpose-There is now considerable evidence that atrial fibrillation is associated with an inflammatory state. We tested the hypothesis that plasma levels of C-reactive protein (CRP; an index of inflammation) and soluble CD40 ligand (an index of platelet activation, with links to inflammation) could be related to 3 established stroke risk stratification schema (SPAF, CHADS 2 , and NICE), recognized stroke risk factors or other cardiovascular disease, and prognosis. Methods-We studied 880 subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
104
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(108 citation statements)
references
References 49 publications
0
104
1
3
Order By: Relevance
“…Recent studies showed that inflammation playes a key role in the initiation, maintenance, and recurrence of AF. 6,7 The neutrophil-lymphocyte ratio (NLR) is a simple, inexpensive, and widely available biomarker. It has been shown that NLR is also a marker of inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that inflammation playes a key role in the initiation, maintenance, and recurrence of AF. 6,7 The neutrophil-lymphocyte ratio (NLR) is a simple, inexpensive, and widely available biomarker. It has been shown that NLR is also a marker of inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…† Significantly different from the low-sCD40L group, P , 0.05. mentioned by us, 5 none of these studies exclusively assessed STEMI patients or variations of sCD40L over time as in the current work. Furthermore, more recent studies not only fail to demonstrate an association of high level of sCD40L with increased risk of cardiovascular events, [21][22][23][24] but in fact, indicate an inverse relation of sCD40L levels with risk of recurrent ischemia. 23 The CD40/CD40L system represents a major costimulator system triggering different signaling pathways mainly attending as amplification of immune and inflammatory responses, 25 including in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of C-reactive protein (CRP), the most widely used biomarker linked to inflammation, demonstrated to be predictive for increased risk for developing atrial fibrillation [24]. Further studies also revealed its association with composite end-point of stroke and death, or composite of ischaemic stroke, myocardial infarction and vascular death [25,26]. Markers of thrombosis and fibrinolysis, including D-dimer and b-thromboglobulin, were predictors of hypercoagulability, and therefore their elevated levels correlated with the risk of thromboembolism (including stroke and systemic thromboembolism) [27].…”
Section: Discussionmentioning
confidence: 99%